Preseptal and Orbital Cellulitis in Childhood: The Experience of Ankara Training and Research Hospital - Zeynep Savaş Şen; Tuğçe Tural Kara; Sevinç Keskin; Gülsüm Özen; Firdevs Örnek; Bülent Alioğlu (Galenos Yayinevi, 2019)
Aim:Evaluation of the etiology, clinical and laboratory findings, treatment and complications of preseptal and orbital cellulitis in patients and to show that these complications can be prevented with early diagnosis and effective treatment.Materials and Methods:Thirty-eight patients with orbital and preseptal cellulitis who had been admitted to Ankara Training and Research Hospital, Clinic of Paediatric between September 2015 and February 2017 were retrospectively studied.Results:Thirty-five patients (92.1%) were diagnosed with preseptal cellulitis and 3 patients (7.9%) were diagnosed with orbital cellulitis. The mean age at diagnosis of the patients [24 girls (63.2%) and 14 boys (36.8%)] was 4.01±3.72 years. The most frequent etiologic factor was conjunctivitis (28.9%). Twenty-five patients (65.7%) were treated with intravenous ampicillin-sulbactam alone as the first treatment. No patient underwent surgery. All patients recovered completely without any eye illnesses and no complications were observed.Conclusion:Orbital infections can be healed through early diagnosis and effective antibiotic therapy in childhood and ampicillin-sulbactam therapy alone should be preferred over combination therapy due to its high effectiveness and relatively low side effects.